Sovereign Debt - Martinez, Leonardo (IMF Working Papers; Working Paper, 2022)
This paper surveys the literature on sovereign debt from the perspective of understanding how sovereign debt differs from privately issue debt, and why sovereign debt is deemed safe in some countries but risky in others. The answers relate to the unique power of the sovereign. One the one hand, a sovereign has the power to tax, making debt relatively safe; on the other, it also has control over its territory and most of its assets, making debt enforcement difficult. The paper discusses debt contracts and the sovereign debt market, sovereign debt restructurings, and the empirical and theoretical literatures on the costs and causes of defaults. It describes the adverse impact of sovereign default risk on the issuing countries and what explains this impact. The survey concludes with a discussion of policy options to reduce sovereign risk, including fiscal frameworks that act as commitment devices, state-contingent debt, and independent and credible monetary policy.